154k views
15 votes
2x+3y)^2– 24xy = (2x-3y)^2

User Nik
by
5.3k points

1 Answer

8 votes

Answer:


\mathrm{True\:for\:all}\:x

Explanation:


\left(2x+3y\right)^2-24xy=\left(2x-3y\right)^2


\left(2x+3y\right)^2-24xy


=4x^2+12xy+9y^2-24xy


=9y^2-12xy+4x^2


\left(2x-3y\right)^2


a=2x,\:\:b=3y


=\left(2x\right)^2-2\cdot \:2x\cdot \:3y+\left(3y\right)^2


=4x^2-12xy+9y^2


9y^2-12xy+4x^2=4x^2-12xy+9y^2


\mathrm{Subtract\:}9y^2\mathrm{\:from\:both\:sides}


9y^2-12xy+4x^2-9y^2=4x^2-12xy+9y^2-9y^2


\mathrm{Simplify}


-12xy+4x^2=4x^2-12xy


\mathrm{Subtract\:}4x^2-12xy\mathrm{\:from\:both\:sides}


-12xy+4x^2-\left(4x^2-12xy\right)=4x^2-12xy-\left(4x^2-12xy\right)


\mathrm{Simplify}


0=0


\mathrm{Both\:sides\:are\:equal}


\mathrm{True\:for\:all}\:x

User Youbetternot
by
6.2k points